"It would be for the best to suspend publication": The German–American Press and Anti-German Hysteria During World War I. Issue 1 (2nd January 2020) - Grieves, Kevin
: During World War I, the German-American press became a lightning rod for anti-German sentiment. New rules required German-language papers to supply English translations, and many publications faced bankruptcy. Some of the most strident attacks came from English-language journalists. Analysis of content of German-language newspapers reveals how editors of those newspapers positioned their publications during World War I, responded to attacks from other journalists, and how they articulated their professional stance in relation to loyalty to the government. Questions about journalists' obligations to expressions of patriotism and support of their government have arisen on a regular basis up to the present, and this research helps shed light on how notions of journalistic independence are reconciled with a sense of patriotic obligation.